2018
DOI: 10.1016/j.ultsonch.2017.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound assisted extraction of phenolic acids from broccoli vegetable and using sonochemistry for preparation of MOF-5 nanocubes: Comparative study based on micro-dilution broth and plate count method for synergism antibacterial effect

Abstract: The aim of this work was comparison study of dilution and plating method for evaluation of the synergism effect of metal-organic framework nanocubes (MOF-5-NCs) and broccoli extract (Brassica oleracea) on antibacterial activity of standard and clinical Pseudomonas aeruginosa strains. For this purpose, sonochemical synthesis of MOF-5-NCs was performed and it was characterized using XRD, FT-IR, FESEM and EDS techniques. Maceration extraction (ME) and ultrasound assisted extraction (UAE) methods in three differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 55 publications
0
28
0
Order By: Relevance
“…Hubbard et al (2017) reported that consumption of broccoli heightened intestinal aryl hydrocarbon receptor activity, decreased microbial abundance of the family Erysipelotrichaceae and attenuated colitis in mice. Pezeshkpour et al (2018) observed that broccoli extract inhibited the growth of standard and clinical Pseudomonas aeruginosa strains. On the other hand, Mustafa & Baurhoo (2016) reported that broccoli floret residues did not affect presumptive bacterial populations in the cecal digesta of broilers.…”
Section: Effect Of Broccoli Residues Fermented With Probiotics On Thementioning
confidence: 99%
“…Hubbard et al (2017) reported that consumption of broccoli heightened intestinal aryl hydrocarbon receptor activity, decreased microbial abundance of the family Erysipelotrichaceae and attenuated colitis in mice. Pezeshkpour et al (2018) observed that broccoli extract inhibited the growth of standard and clinical Pseudomonas aeruginosa strains. On the other hand, Mustafa & Baurhoo (2016) reported that broccoli floret residues did not affect presumptive bacterial populations in the cecal digesta of broilers.…”
Section: Effect Of Broccoli Residues Fermented With Probiotics On Thementioning
confidence: 99%
“…Diluted samples were cultured onto Muller Hinton agar to assess the number of colonies by a colony counter (TAT-Ko, Teifazmateb,Tehran). To count the number of bacteria on the plate, the following formula was used: 38 N × b = m…”
Section: The Effect Of Absorption Process On the Reduction Of Biofilmmentioning
confidence: 99%
“…MOF‐5 has adjustable three‐dimensional frame structure formed by [Zn 4 O] group and phenylenedimethylene, whose metal nodes can act as Lewis acid catalysts . In addition, some functional species such as Pt, Au and Pd et al are loaded to form MOF‐based metal catalysts .…”
Section: Introductionmentioning
confidence: 99%